PENERAPAN APLIKASI PEMBELAJARAN BAHASA INGGRIS DASAR BERBASIS MULTIMEDIA - Winia Waziana; Leni Anggraeni; Nur Laela Sari (Jurnal TAM (Technology Acceptance Model), 2016)
The low interest in learning English in primary school, one of which is influenced by learning methods applied by teachers in conventional, it causes the students find it difficult to understand the subject matter of English. Basic English learning method requires the application of the fun that can foster student interest and make it easier to understand the subject matter, one of them with the implementation of interactive multimedia learning media in the form of applications / software-based computer. The scope of the problem in this research is how to create interactive multimedia learning media in the form of applications / software, computer-based, in order to facilitate students in understanding the subject matter of English. The method used is the method of literature, observation, interviews, analysis, project design, testing and implementation. With the interactive multimedia learning media will be useful for students and make it easier to understand basic English language learning materials.